2016
DOI: 10.1177/2055217316665406
|View full text |Cite
|
Sign up to set email alerts
|

Risk attitudes and risk perceptions in individuals with multiple sclerosis

Abstract: BackgroundLittle is known about risk attitudes and risk perceptions in multiple sclerosis (MS).ObjectivesThe objectives of this paper are to investigate the range of risk attitudes and risk perceptions and examine associations between risk attitudes and risk perceptions and demographic and clinical features of the disease.MethodsA total of 223 individuals completed a risk questionnaire. Risk attitude was measured using two rating scales and a standard gamble scenario. Risk perception was measured by asking par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…9 Another study used the standard gamble paradigm to evaluate RT to death. 15 Those investigators observed male sex, greater disability, and longer disease duration to be associated with greater tolerance to risk of death. We found a similar association with sex and disability but not disease duration.…”
Section: Discussionmentioning
confidence: 98%
“…9 Another study used the standard gamble paradigm to evaluate RT to death. 15 Those investigators observed male sex, greater disability, and longer disease duration to be associated with greater tolerance to risk of death. We found a similar association with sex and disability but not disease duration.…”
Section: Discussionmentioning
confidence: 98%
“…A consent form was followed by a short, single-page set of travel habit and demographic questions: frequency of travel by different modes, age, gender, home postal code, educational attainment, and household income. Risk aversion was self-assessed with the question “Overall, how would you place yourself on the following scale?” with a seven-point response scale from “Extremely comfortable taking risks” to “Extremely uncomfortable taking risks,” based on Glanz et al ( 45 ). Participants were then shown a series of randomly ordered pages, each with a short (7–18 s) video clip of a sample interaction followed by a prompt to indicate their agreement with four statements about the interaction shown in the video (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…An online questionnaire was implemented in Qualtrics survey software to collect the interaction ratings. A (45). Participants were then shown a series of randomly ordered pages, each with a short (7-18 s) video clip of a sample interaction followed by a prompt to indicate their agreement with four statements about the interaction shown in the video (see Figure 1).…”
Section: Rating Surveymentioning
confidence: 99%
“…Therefore, Risk attitude is described as an individual enlightenment towards either avoiding or preferring risk when deciding on how to proceed in the circumstances embedded with the uncertain outcome. (Glanz, Greeke, LaRussa, Stuart, Rintell, Chitmis, & Healy, 2016). Risk attitude functions as an individual perception of risk with the tendency of experiencing an adverse event (Lippi, Barbieri, Piva, & De Bondt, 2018).…”
Section: Risk Attitudesmentioning
confidence: 99%